2010
DOI: 10.1111/j.1526-100x.2008.00437.x
|View full text |Cite
|
Sign up to set email alerts
|

Moss Regeneration for Fen Restoration: Field and Greenhouse Experiments

Abstract: Fen bryophytes are an important component of natural fens and should be included in fen restoration projects. The goal of this study was to examine the regeneration capabilities of nine bryophytes common to moderate-rich and poor fens in North America. A greenhouse experiment was carried out to examine the limitations and optima for the regeneration of fen bryophytes under different light and water regimes. A field experiment tested these same bryophytes in the presence of three potential nurse-plants. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 46 publications
(45 reference statements)
2
33
0
Order By: Relevance
“…This is an effective mechanism to tolerate desiccation, but metabolism (photosynthesis, growth) can only occur when water is available and the plant is hydrated (Proctor, 2000;Robinson et al, 1989). Several studies have shown that atmospheric water availability is more important to bryophytes than the moisture level of the soil because bryophytes absorb water with their entire above-ground surface (Graf and Rochefort, 2010;Klepper, 1963). We found a positive relationship of soil moisture with soil bryophyte abundance and species richness.…”
Section: The Importance Of Soil Moisturementioning
confidence: 75%
“…This is an effective mechanism to tolerate desiccation, but metabolism (photosynthesis, growth) can only occur when water is available and the plant is hydrated (Proctor, 2000;Robinson et al, 1989). Several studies have shown that atmospheric water availability is more important to bryophytes than the moisture level of the soil because bryophytes absorb water with their entire above-ground surface (Graf and Rochefort, 2010;Klepper, 1963). We found a positive relationship of soil moisture with soil bryophyte abundance and species richness.…”
Section: The Importance Of Soil Moisturementioning
confidence: 75%
“…in a 10-km square), but also local climate and habitat conditions, as these determine the survival and establishment of the transplants (Gunnarsson and Söderström 2007;Graf and Rochefort 2010). In this study, transplanted bundles of shoots grew independent of microhabitat type, only a very small negative influence of cover of grasses on growth was indicated.…”
Section: Is the Distribution Of H Hutchinsiae Limited By Habitat Avamentioning
confidence: 87%
“…However, transplanted fragments of H. hutchinsiae have been shown to grow better between other bryophytes than in other microhabitats (Flagmeier et al 2013). Graf and Rochefort (2010) similarly reported an effect of microhabitat on transplants of Sphagnum with fragments regenerating better under a dense canopy of herbaceous plants. Hence, even if vegetation type were not critical for population persistence, the success of fragment establishment and growth, and therefore population expansion, may be influenced by the surrounding vegetation.…”
Section: Is the Distribution Of H Hutchinsiae Limited By Habitat Avamentioning
confidence: 95%
See 1 more Smart Citation
“…Agricultural straw mulch and to a lesser extent herbaceous plants have been used as a cover treatment for mosses in peatland restoration projects in eastern Canada (Rochefort et al . ; Graf & Rochefort ), but the effect of vascular plant and woody material cover on moss establishment on mineral sediment remains untested.…”
Section: Introductionmentioning
confidence: 99%